Impact of allopurinol use on urate concentration and cardiovascular outcome - Wei, Li; Mackenzie, Isla S.; Chen, Yang; Struthers, Allan D.; MacDonald, Thomas M. (British journal of clinical pharmacology, 2011)
WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Guidelines recommend that the therapeutic goal of urate‐lowering therapy (ULT) is to achieve a urate concentration of ≤6 mg dl−1. • High‐dose allopurinol is associated with reduced cardiovascular events and mortality in heart failure patients. WHAT THIS STUDY ADDS • Less than 50% of patients taking allopurinol reached target urate concentration. • Higher doses of allopurinol were associated with better control of urate and lower risks of both cardiovascular events and mortality in all patients on allopurinol treatment. AIMS To characterize patients with urate measurements by urate‐lowering therapy (ULT) use and to study the impact of allopurinol treatment on cardiovascular and mortality outcomes. METHODS A cohort study using a record‐linkage database. The study included 7135 patients aged ≥60 years with urate measurements between 2000 and 2002 followed up until 2007. A Cox regression model was used. The association between urate levels, dispensed allopurinol and cardiovascular hospitalization and mortality was determined. RESULTS Six thousand and forty‐two patients were not taking ULT and 45.9% of those (2774 of 6042) had urate concentrations ≤6 mg dl−1. Among 1035 allopurinol users, 44.7% (45.6% for men and 43.3% for women) reached target urate concentration. There was no significant increased risk of cardiovascular events for allopurinol users when compared with non‐ULT users [adjusted hazard ratio (HR) 1.10, 95% confidence interval (CI) 0.95–1.26] and the non‐ULT group with urate >6 mg dl−1 (adjusted HR 1.07, 95% CI 0.89–1.28). Within the allopurinol use cohort, cardiovascular event rates were 74.0 (95% CI 61.9–86.1) per 1000 person years for the 100 mg group, 69.7 (49.6–89.8) for the 200 mg group and 47.6 (38.4–56.9) for the ≥300 mg group. Compared with low‐dose (100 mg) users, high‐dose (≥300 mg) users had significant reductions in the risk of cardiovascular events (adjusted HR 0.69, 95% CI 0.50–0.94) and mortality (adjusted HR 0.75, 95% CI 0.59–0.94). CONCLUSIONS Less than 50% of patients taking allopurinol reached target urate concentration. Higher doses of allopurinol were associated with better control of urate and lower risks of both cardiovascular events and mortality.